The Impact of the Implementation of E-Learning in Thematic Learning on the Academic Achievement Progress of Senior School Students - Reza Pahlevi; Mateus De Jesus Ximenes; Dk. Nurul Najiah Pg Abu Bakar (Indonesian Journal of Innovative Teaching and Learning, 2026)
Background: The increasing use of smartphones among elementary school students has raised concerns about their potential impact on learning engagement and academic behaviours, as excessive smartphone use may reduce students’ focus, discipline, and interest in schoolwork. Objective: This study aimed to examine the effect of limiting smartphone use on students’ learning interest at the elementary level. Method: The research employed an ex post facto design conducted at SMAN 1 Batujajar in 2025, involving 31 students as the research sample. Data were collected using a smartphone use restriction scale and a learning interest scale. Statistical analysis was performed using simple linear regression to determine the influence of smartphone use limitation on students’ learning interest. Results: The t-test showed a p-value of 0.000, which is lower than 0.05 (0.000 < 0.05). This indicates that limiting smartphone use has a statistically significant effect on students’ learning interest. Conclusion: Smartphone use restriction contributes positively to improving students’ learning interest. Contribution: This study provides empirical evidence regarding the relationship between smartphone use limitation and learning interest. The findings offer practical implications for teachers and schools in formulating smartphone-use policies and contribute to theoretical discussions of digital behaviour and student engagement in elementary education.